The Search for Major John Richardson’s Unknown Writings - Beasley, David (Ontario History, 2021)
This article will identity three anonymous works written by novelist Major John Richardson whose authorship has been assigned to others. A detailed knowledge of Richardson‘s activities, friendships, and aspirations as related to his writings will be one tool; another will be an analysis of the style and matter of the texts as they compare to works known to have been written by Richardson, a man widely recognized as the father of Canadian literature.